Accuracy of anogenital distance and anti‐Müllerian hormone in the diagnosis of endometriosis without surgery. Issue 1 (24th October 2018) - Sánchez‐Ferrer, María L.; Jiménez‐Velázquez, Raquel; Mendiola, Jaime; Prieto‐Sánchez, María T.; Cánovas‐López, Laura; Carmona‐Barnosi, Ana; Corbalán‐Biyang, Shiana; Hernández‐Peñalver, Ana I.; Adoamnei, Evdochia; Nieto, Aníbal; Torres‐Cantero, Alberto M.
Abstract: Objective: To assess the predictive ability of a combination of anogenital distance (AGD) and anti‐Müllerian hormone (AMH) to diagnosis the presence of endometriosis without surgery. Methods: The present study included women diagnosed with endometriosis and a control group who attended the "Virgen de la Arrixaca" University Hospital, Murcia, Spain, between September 1, 2014, and May 31, 2015. Serum concentrations of AMH were measured, and two AGD measurements were obtained: from the anterior clitoral surface to the upper verge of the anus (AGDAC ), and from the posterior fourchette to the upper verge of the anus (AGDAF ). Data were assessed by receiver operator characteristic (ROC) curves. Results: Women in the endometriosis group (n=57) had significantly shorter AGDAF (22.8 ± 4.6 vs 27.2 ± 5.7 mm; P <0.001) and lower AMH (2.2 ± 2.5 vs 3.3 ± 1.9 ng/mL; P <0.003) compared with the control group (n=93). Women with serum AMH below the clinical cut‐off (1 ng/mL) were 17.40‐times more likely to have endometriosis (95% confidence interval [CI] 5.64–53.82). The area under the ROC curve of combined AMH and AGDAF was 0.77 (95% CI 0.70–0.85). Conclusion: The model for predicting endometriosis on the basis of AMH and AGD could be useful for clinicians and epidemiologists to improve diagnosis and prognosis of this condition. Abstract : Anti‐Müllerian hormone and anogenital distance were found to be useful in the diagnosis of endometriosis.